Effects of Land Fires on Peat Soil Characteristics in Landasan Ulin District, Banjarbaru City - Ellisa, Ellisa; Arisanty, Deasy; Muhaimin, Muhammad (JPG (Jurnal Pendidikan Geografi), 2024)
Peat is a type of soil that has a dry condition, which causes it to burn easily. When the peat is burned, the spread of fire will occur very quickly until it reaches the ground, because peat soil does not contain solid soil, but branches, grass, and tree debris. Even though the fire on the surface has been extinguished, the fire that is in the inner layer is not necessarily extinguished. This study aims to determine the effect of land fires on the characteristics of peat soil in Landasan Ulin District, Banjarbaru City, including the physical and chemical properties of the peat soil. This research uses quantitative methods with a descriptive approach. Primary data in this study include: texture, color, bulk density (BD), soil structure, pH, and nutrients. Primary data collection was in the form of field surveys by looking at peatlands and the physical and chemical characteristics of the soil with 14 samples taken at 7 sample points. The results showed that on peatlands that had been burned, there was an increase in the value of BD, pH, and soluble Fe so that the potential for absorbing and distributing water was low, and plant roots were difficult to absorb nutrients. Organic C content also decreased, causing soil fertility to decrease.